The Fourteenth Marcel Grossmann Meeting 2017
DOI: 10.1142/9789813226609_0044
|View full text |Cite
|
Sign up to set email alerts
|

Photospheric emission in gamma-ray bursts

Abstract: A major breakthrough in our understanding of gamma-ray bursts (GRB) prompt emission physics occurred in the last few years, with the realization that a thermal component accompanies the over-all nonthermal prompt spectra. This thermal part is important by itself, as it provides direct probe of the physics in the innermost outflow regions. It further has an indirect importance, as a source of seed photons for inverse-Compton scattering, thereby it contributes to the nonthermal part as well. In this short review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 184 publications
(332 reference statements)
0
3
0
Order By: Relevance
“…Although more detailed calculations performed by [364,365] have demonstrated that the internal-shock model which includes benchmark parameters (e.g., the bulk Lorentz factor Γ B = 300) is consistent with the upper limits obtained by IceCube, these results have posed more stringent constraints on the internal shocks model because there is a possible correlation between the bulk Lorentz factor Γ B and the GRB luminosity [366,367,368]. Instead, alternative scenarios in the context of the ultra-relativistic jet model are the photospheric emission model [369,370,371,372,373], and the Internal-Collision-induced MAgnetic Reconnection and Turbulence (ICMART) model [374,375]. Photospheric models assume that thermal energy stored in the jet is radiated as prompt emission at the Thomson photosphere [376,377,378], while ICMART models envisage that collisions between "mini-shells" in a Poynting-flux-dominated outflow distorts the ordered magnetic field lines in a run-away manner, which accelerates particles that then radiate synchrotron γ-ray photons at radii of ∼ 10 15 − 10 16 cm [374,375].…”
Section: Central-engine Models -Millisecond Magnetars Vs Collapsarsmentioning
confidence: 61%
“…Although more detailed calculations performed by [364,365] have demonstrated that the internal-shock model which includes benchmark parameters (e.g., the bulk Lorentz factor Γ B = 300) is consistent with the upper limits obtained by IceCube, these results have posed more stringent constraints on the internal shocks model because there is a possible correlation between the bulk Lorentz factor Γ B and the GRB luminosity [366,367,368]. Instead, alternative scenarios in the context of the ultra-relativistic jet model are the photospheric emission model [369,370,371,372,373], and the Internal-Collision-induced MAgnetic Reconnection and Turbulence (ICMART) model [374,375]. Photospheric models assume that thermal energy stored in the jet is radiated as prompt emission at the Thomson photosphere [376,377,378], while ICMART models envisage that collisions between "mini-shells" in a Poynting-flux-dominated outflow distorts the ordered magnetic field lines in a run-away manner, which accelerates particles that then radiate synchrotron γ-ray photons at radii of ∼ 10 15 − 10 16 cm [374,375].…”
Section: Central-engine Models -Millisecond Magnetars Vs Collapsarsmentioning
confidence: 61%
“…Preece et al 1998b;Ghirlanda, Celotti & Ghisellini 2002; ⋆ E-mail: gabriele.ghisellini@inaf.it 2014; Yu et al, 2016). Rarely, the very hard low energy spectra have been reproduced with a thermal component: in a few cases with a pure black body spectrum (Ghirlanda, Celotti & Ghisellini 2004;Ghirlanda, Pescalli & Ghisellini 2013); more often with a power law or a Band model with the addition of a black body contribution (Ryde & Pe'er 2009;Ryde et al 2010;Guiriec et al 2011;Burgess et al 2014;Pe'er & Ryde 2017; but see Ghirlanda et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A similar mechanism operates in the cannonball model (Dado et al 2007) which advocates bulk Comptonisation as the primary source of GRB prompt emission. On the other hand, evidence of thermal photospheric emission has been reported in many cases of prompt GRB emission (Pe'er & Ryde 2016). This component, while potentially providing seed photons for Compton drag, would by itself contribute little to polarized emission and hence reduce the overall degree of polarisation.…”
Section: Polarisationmentioning
confidence: 99%